Length-weight relationships and condition factors of brackish water catfish, Mystus gulio (Hamilton, 1822) from three different estuaries, West Java, Indonesia - EPA PAUJIAH; YAYAT DHAHIYAT; TITIN HERAWATI; ISKANDAR ISKANDAR; HARYONO HARYONO; ILHAM ZULFAHMI; FAHRI FAHRI (Society for Indonesian Biodiversity, 2023)
Abstract. Paujiah E, Dhahiyat Y, Herawati T, Iskandar, Haryono, Zulfahmi I, Fahri. 2023. Length-weight relationships and condition factors of brackish water catfish, Mystus gulio (Hamilton, 1822) from three different estuaries, West Java, Indonesia. Biodiversitas 24: 2855-2864. This study investigated the biometric condition of brackish water catfish (Mystus gulio Hamilton 1822) collected from three different estuaries in Cianjur District, West Java Province, Indonesia. Data (class interval, growth pattern, and factor condition) were sorted based on time, location, and season. Water quality parameters measured include temperature, conductivity, TDS, hardness, resistivity, pH, DO, total oxygen, ORP, and salinity. The correlation between K-Value and water quality parameters was analyzed using multivariate analysis. Our results showed that the worth pattern of M. gulio was allometric, with condition factors value ranging from 0.904-1.042. There were variations in the growth patterns according to time, location, and fish sex. The lowest condition factor values were found in August for males and April for females. Meanwhile, the highest condition factor values were found for males on 4 June 2022 and 5 February 2022 for females. The NMDS analysis places the water resistivity and conductivity on a different axis from other environmental factors. The results of our study suggest that the estuaries in Cianjur District were adequate for supporting the survival and growth of M. gulio by providing food and suitable habitat.